IMPROVING STUDENT LEARNING AWARENESS USING RATIONAL EMOTIVE BEHAVIOR THERAPY TECHNIQUES AT VOCATIONAL SCHOOL OF DARUL ANWAR, BANYUWANGI REGENCY CITY EAST JAVA INDONESIA - Agus Mursidi; Harwanti Noviandari; Mujibburohman; Mislan (International Jurnal of Education Schoolars, 2020)
Low is due to low self-awareness of students. On the one hand, low self-awareness is caused because students have irrational thoughts about lessons and how they learn. Thinking that learning is very boring, not fun, studying or studying is something that is not important, the thought that we can also be successful without learning. The research used is a quantitative type, using lots of numbers, starting from data collection, interpretation of the data, and the appearance of the results. Likewise, research conclusions are still used if they are accompanied by tables, graphs, charts, pictures or other views. The method used in this research is pre-experimental research. The reason the researcher uses this method is because in the pre-experimental method design, the researcher observes one main group by intervening in it throughout the study, besides that in this method, it does not use a control group to be compared with the experimental group. The result is that group counseling with a behavioral approach to the technique of Rational Emotive Behavior Therapy has an effect on increasing the awareness of class XI TKJ TKJ SMK Darul Anwar.